Dataset of ideological polarization in Western Europe - Emanuele, Vincenzo; Marino, Bruno (2023)
This dataset provides data on ideological polarization in Western Europe. It is based on parties’ left-right placement provided by several expert surveys and then uses Dalton’s polarization index (2008) to calculate the polarization score in terms of votes and seats for each election. The dataset covers 20 Western European countries since 1945, for a total of 398 parliamentary elections and legislatures (Lower House). The dataset will be regularly updated to include the polarization scores of new elections and legislatures. This dataset provides data on ideological polarization in Western Europe. It is based on parties’ left-right placement provided by several expert surveys and then uses Dalton’s polarization index (2008) to calculate the polarization score in terms of votes and seats for each election. The dataset covers 20 Western European countries since 1945, for a total of 398 parliamentary elections and legislatures (Lower House). The dataset will be regularly updated to include the polarization scores of new elections and legislatures.